Malaysian perception and attitude towards electric vehicle - Rafia, Afroz; Rahman, Mohammed Ataur (2013)
It is noticeable that environmental problems are now becoming global issue. Automotive industries are one of the major contributors to environmental problems. Harmful gases released and waste of automobile polluted the quality of air and damaging the environment. Because of excessive consumption of fossil fuels leads to greenhouse gases emission and causing various environmental problems. Since Malaysia’s automotive production increasing rapidly compared to other Asian countries. Therefore, there is a pressing need to examine Malaysian vehicle users’ level of intention, major factors to influence to buy and barriers for green technology. Hence, the aim of this research paper is to investigate vehicle users’ level of intention, major influencing factors and obstacles to purchase green car in Malaysia. The findings of this study indicate that there is a significant relationship between age group, education and attitudes towards EVs. It also revealed that the significant relationship between purchase intention and demographic variables such as age group, education and gender. Therefore, the results from this study can be used to provide important insights for policy-makers in developing programs or projects to increase consumers’ awareness, removing obstacles and focus on major influential factors for having environment friendly automotive industries in Malaysia.